2017
DOI: 10.1016/j.expneurol.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Insulin prevents aberrant mitochondrial phenotype in sensory neurons of type 1 diabetic rats

Abstract: Diabetic neuropathy affects approximately 50% of diabetic patients. Down-regulation of mitochondrial gene expression and function has been reported in both human tissues and in dorsal root ganglia (DRG) from animal models of type 1 and type 2 diabetes. We hypothesized that loss of direct insulin signaling in diabetes contributes to loss of mitochondrial function in DRG neurons and to development of neuropathy. Sensory neurons obtained from age-matched adult control or streptozotocin (STZ)-induced type 1 diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 75 publications
(96 reference statements)
3
21
0
2
Order By: Relevance
“…It has also been proposed that loss of insulin signaling is involved in the development of mitochondrial changes of DRGs [126,133,134]. Interestingly, a recent study has revealed that insulin promotes mitochondrial gene expression of cultured DRG neurons derived from control and STZ-diabetic rats [135]. Additionally, it has also been demonstrated that insulin treatment enhanced thermal sensitivity and increased dermal nerve density in diabetic animals [135].…”
Section: Role Of Trpv1 Receptor Insr and Insulin In The Development mentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been proposed that loss of insulin signaling is involved in the development of mitochondrial changes of DRGs [126,133,134]. Interestingly, a recent study has revealed that insulin promotes mitochondrial gene expression of cultured DRG neurons derived from control and STZ-diabetic rats [135]. Additionally, it has also been demonstrated that insulin treatment enhanced thermal sensitivity and increased dermal nerve density in diabetic animals [135].…”
Section: Role Of Trpv1 Receptor Insr and Insulin In The Development mentioning
confidence: 99%
“…Interestingly, a recent study has revealed that insulin promotes mitochondrial gene expression of cultured DRG neurons derived from control and STZ-diabetic rats [135]. Additionally, it has also been demonstrated that insulin treatment enhanced thermal sensitivity and increased dermal nerve density in diabetic animals [135]. It has also been shown that chronic administration of fructose, which induces insulin resistance, and neuropathic pain, reduced InsR protein expression in DRGs and sciatic nerve [123].…”
Section: Role Of Trpv1 Receptor Insr and Insulin In The Development mentioning
confidence: 99%
“…Given these growth supportive roles of insulin in peripheral neurons, we have hypothesized that deficiency of insulin–PI3K–Akt trophic support during insulinopenic diabetes mellitus influences the development of DPN. For example, direct neuronal or axonal insulin administration, even if insufficient to alter blood glucose levels, reverses diabetic neuropathic changes in type 1 diabetes mellitus models that are characterized by the absence of the insulin ligand.…”
Section: Direct Neuronal Involvement Of Diabetes: Insulin Glucagon‐lmentioning
confidence: 99%
“…Male C57BL/ksj-db/db mice (7-8 weeks, blood glucose concentration 20mmol/L, Shanghai Silaike Experimental Animals LTD) and the C57BL/6 mice (7-8weeks) fed and maintained under constant SPF conditions and temperature 23±2℃, humidity 50±5%, with 12h light and 12h dark cycles. In the mouse experiment, diabetic mice were divided into 5 groups : (1) wild type group for db/db mice (normal control, n=10), (2) diabetic mice treated with PBS (model control, n=10), (3) diabetic mice treated with FGF21 (0.5mg/kg, n=10), (4) diabetic mice treated with FGF21 (1.0mg/kg, n=10), (5) diabetic mice treated with FGF21 (2.0mg/kg, n=10). PBS or FGF21 injected into the mice once daily for four months.…”
Section: Animals and Treatment Regimensmentioning
confidence: 99%
“…Diabetes and AD shared corporate abnormalities, including impaired glucose metabolism, increased oxidant stress, chronic inflammation, insulin resistance, aggregation of Amyloid and Tau protein [4]. The diabetes and aging mice have provided a relevant animal model for nerve damage, and developed many AD-like neuropathological features, including inhibited AKT, aggregation of Tau protein and glycogen synthase kinase-3β (GSK-3β) overactivation [5,6]. The db/db mice were used usually [7].…”
Section: Introductionmentioning
confidence: 99%